2017
DOI: 10.1177/1056492617710758
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-First Century Leadership: A Return to Beauty

Abstract: Highlighting Aristotle’s appreciation that “The soul . . . never thinks without a picture,” this article weaves together art and ideas into an aesthetic encounter with beauty, leadership, and our humanity. It invites reflection based on long-established wisdom traditions as well as drawing on insights from everyday sacred traditions. You are invited not only to engage in reading the words presented on each page but also to stop and to reflect on their meaning. You are offered the power of art to intensify your… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…More recently, Nancy Adler has made something of a campaign to alert us to an imperative for beauty in leadership (Adler, 2006(Adler, , 2011Adler & Delbecq, 2018). Latham (2014, pp.…”
Section: The Art In Organization Leadershipmentioning
confidence: 99%
“…More recently, Nancy Adler has made something of a campaign to alert us to an imperative for beauty in leadership (Adler, 2006(Adler, , 2011Adler & Delbecq, 2018). Latham (2014, pp.…”
Section: The Art In Organization Leadershipmentioning
confidence: 99%
“…Creative mediums act as visual, aural, kinesthetic, and tactile aids that help audiences in perceiving, conceptualizing, and personally relating to the research (Bresler, 2009). Weaving together words and images opens a new world of meaning to the audience by integrating intellectual thoughts with emotional reactions (Adler & Delbecq, 2018), creating a sum which is greater than each component (Gerstenblatt, 2013). This allows people to connect on different levels, beyond the intellectual (Hatch, 2017), for increased empathy between practitioners and academic researchers, which in turn facilitates dissemination and understanding (Nonaka, 1994; Nonaka & Takeuchi, 1995; Rynes, Bartunek, & Draft, 2001).…”
Section: “Those Are My Words That’s Me!” Creative Mediums Foster a Mmentioning
confidence: 99%
“…Researchers presenting at conferences can use visuals to enhance their Power Point presentations as Natalia Korchagina and Alison Pullen did at the 2016 Academy of Management Conference (see Image 10 in Figure 1); they showed artwork (animated images, paintings, and pictures) to convey the deconstructionist position and writing style of the author they were studying—post-modern French philosopher Jean-Luc Nancy. In the footsteps of Adler and Delbecq (2018, p. 3) who designed an “aesthetic leadership reflection” articulating paintings, texts, and mindfulness, authors should “go beyond words” to holistically “engage the head and the heart” of the readership. Conference organizers can consider creating tracks for presentations using creative mediums as the organizers of the Association for Consumer Research Conference did with the Videography Track.…”
Section: Let’s Perform and Paint!mentioning
confidence: 99%
“…For some time now, the literature has described leadership as an art (e.g., Grint, 2000;Ladkin & Taylor, 2010;Springborg, 2010) or as artistic practice (e.g., Adler, 2011, Adler & Delbecq, 2018Berthoin Antal, Debucquet, & Frémeaux, 2017;Ladkin, 2006Ladkin, , 2008. The literature has also suggested that leadership should be researched (Latham, 2014) and developed (Berthoin Antal et al, 2017;Edwards, Elliott, Iszatt-White, & Schedlitzki, 2015) through artistic means.…”
Section: Artmentioning
confidence: 99%